Parents' attitudes towards hepatitis B vaccination for their children. A survey comparing paper and web questionnaires, Sweden 2005 - Tegnell Anders; Dannetun Eva; Giesecke Johan (BMC, 2007)
Abstract Background The World Health Organisation, WHO, recommends that most countries should vaccinate all children against hepatitis B. Sweden has chosen not to do so, but the issue is reassessed regularly. The objective of this survey was to assess knowledge and attitudes towards hepatitis B vaccine for children among parents living in Sweden, and to compare distribution of responses and response rate between parents answering a postal questionnaire and those responding via the Internet. Methods A population-based cross-sectional survey, where the sampling frame consisted of all parents to a child born 2002 living in Sweden. Two independent samples of 1001 parents in each sample were drawn. All parents were contacted by postal mail. The parents in the first sample were invited to participate by answering a paper questionnaire. The parents in the second sample were given an individual user name along with a password, and asked to log on to the Internet to answer an identical electronic questionnaire. Results A total of 1229 questionnaires were analysed. The overall response rate for paper questionnaires was 55%, and 15% for the web version. Knowledge of the disease hepatitis B was overall high (90%). A higher degree of knowledge was seen among parents with education beyond high school (p = 0.001). This group of parents also had a higher tendency to reply via the Internet (p = 0.001). The willingness to accept hepatitis B vaccine for their child was correlated to the acceptance of the present childhood vaccination programme (p = 0.001). Conclusion The results reveal a high level of knowledge of the disease and a positive attitude to having their children vaccinated. This study also displays that the conventional postal method of surveying still delivers a higher response rate than a web-based survey.